Development of miniature jet engine test rig - Tan, Beng Keat. (2011)
In this project, a general-purpose ground level jet engine test cell was designed and developed. The design is a conversion of an existing MiniLab™ Test Bench from Turbine Technologies Ltd. This project expands the test capability of the MiniLab™ which is limited to test the SR-30 Jet engine only.